Cleaning Preparation of Ni/C Nanocomposites and Enhanced Electromagnetic Properties. Issue 2 (May 2019) - Zhang, Nan; Li, Jinfeng; Li, Zhigang; Wang, Qiang; Zhao, Hongtao
Abstract: Carbon/magnetic-metal composites with excellent properties have become an important development trend and research hot-spot in the field of microwave absorbing materials. By using polypyrrole as carbon source, the electromagnetic functionalized Ni/C nanocomposites were prepared by carbonization treatment assisted with in-situ oxidation polymerization and γ-irradiation induced reduction technique. The structure and morphology of the composites were characterized by XRD, SEM and TEM analysis, respectively. The electromagnetic properties of the composites in the frequency range of 2-18 GHz were studied by mixing the composites with paraffin by the mass ratio of 1:4. The maximum RL of the composite was up to -44 dB at 14.4 GHz with the thickness of 2.5 mm and the absorption bandwidth under -10 dB was 6.5 GHz. The excellent EM absorption performance was attributed to an appropriate impedance matching and interfacial polarization.